2019
DOI: 10.1108/arla-02-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

Understanding affective evaluation in retail: consumers perspective

Abstract: Purpose The purpose of this paper is to analyze the effect of the consumer’s emotional shopping experience on the perception of benefits and on the corporate reputation of a department store. Design/methodology/approach This study was applied to a non-probabilistic sample survey proportionally distributed among the main department stores in Chile and Mexico. Findings The findings show for both countries that the functional and symbolic benefit perceived by consumers significantly influences the reputation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 105 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…Inconsistent with extant studies, the effect showed that the development of destination image does not lead visitors to believe that a destination can fulfill all their promises, which could seal a mutual relationship between a destination and its visitors. For instance, previous studies such as Endah et al (2017) and Marinao et al (2012) found a significant influence of destination image on trust, and that satisfaction significantly influences trust. Our findings show that destination image alone does not stimulate trust and may not, on its own, lead to stronger ties and successful future relationships.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Inconsistent with extant studies, the effect showed that the development of destination image does not lead visitors to believe that a destination can fulfill all their promises, which could seal a mutual relationship between a destination and its visitors. For instance, previous studies such as Endah et al (2017) and Marinao et al (2012) found a significant influence of destination image on trust, and that satisfaction significantly influences trust. Our findings show that destination image alone does not stimulate trust and may not, on its own, lead to stronger ties and successful future relationships.…”
Section: Discussionmentioning
confidence: 95%
“…This must be coupled with the destination's safety and the destination's facilities' comfort and the convenience (Marinao et al, 2017). In their research on components of trust in Chile, Marinao et al (2012) found that perceived image assists as a background influence of trust. Therefore, it is proposed that H3.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…They were adapted from an earlier published studies (Kaplanidou, K & Vogt, 2006;Koo, 2013;Jensen, 2016;Hsu, et.al.2020). The fourth part was for Tourist Trust (TT) that was containing 9 items and they were taken from (Marinao, Chasco & Torres 2012). The fifth part was about Quality Of Life (QOL).…”
Section: Methodology Population Sample and Designmentioning
confidence: 99%
“…In tourist destinations, Trust is a multidimensional concept amongst three parties; local inhabitants and tourist public and private institutions. It is about honesty, benevolence, and competence of the core factors linked to the tourist destinations in terms of meeting tourist needs ( Marinao, Chasco & Torres, 2012;Artigas et al, 2017;Primananda, et.al., 2022). According to trust transfer theory, positive image and positive attitude towards events have a positive impact on trusting destinations and behavioral intentions.…”
Section: Tourist Trust (Tt)mentioning
confidence: 99%
“…When a destination becomes popular in the minds of a tourist because of how much knowledge he or she has about it, it will naturally link to an array of benefits and positive expectations about quality, reliability, and trust (Horng et al, 2012). Tourism studies conceptualize destination trust as a multidimensional construct, which can refer to local residents and public and private institutions being perceived as honest, benevolent, and competent (Marinao et al, 2012) or tourists' confidence and certainty toward tourism services or offerings (Al-Ansi & Han, 2019). According to the theory of sociology of trust and risk proposed by Luhmann (1979Luhmann ( , 1988Luhmann ( , 2000, familiarity affects trust.…”
Section: Subjective Knowledgementioning
confidence: 99%